Aplikasi Tes Online (ATOS) Media Latihan Ujian Nasional Berbasis Komputer untuk Siswa Kelas XII SMK PGRI 1 Giri Banyuwangi - Mohammad Erdda Habiby; Sony Panca Budiarto (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2019)
Computer-Based National Examination (UNBK) also called the Computer Based Test (CBT) is a system of implementing national examinations using computers as the test media. The implementation of UNBK is still not optimal, especially in district cities or remote areas. SMK PGRI 1 Giri is one of the schools in Banyuwangi Regency with a low graduation rate. Some of the causes of the decline in the value of computer-based national exams in Banyuwangi is the panic of students because they are not accustomed to working on the questions in the time listed on the monitor that makes students nervous, the other cause is some students are not accustomed to working on computer-based exam questions. Based on the above problems, it is necessary to develop a computer-based exam application that is designed to have a work principle and appearance that is almost the same as the computer-based national examination system (UNBK). In this study, the Online Test Application (ATOS) was designed using PHP and MySQL with the waterfall development method, so that it can be used by Teachers to train students computer-based exams.